Single-cell mitophagy patterns within the tumor microenvironment modulate intercellular communication, impacting the progression and prognosis of hepatocellular carcinoma - Li, Zhengyan; Chen, Wei; Yao, Shu; Peng, Zuxiang; Liu, Hongming; Tang, Yongliang; Feng, Yi (Frontiers in Immunology, 2025)
Hepatocellular carcinoma (HCC) is a common malignant tumor of the digestive system with a high incidence that seriously threatens patients' lives and health. However, with the rise and application of new treatments, such as immunotherapy, there are still some restrictions in the treatment and diagnosis of hepatocellular carcinoma, and the therapeutic effects on patients are not ideal. Hence, investigating the pathomechanism and identifying novel diagnostic and treatment methods are important. In this study, a comprehensive single-cell analysis of mitophagy-related genes of hepatocellular carcinoma was conducted using the non-negative matrix decomposition method. Within the mitophagy patterns, there are complex cellular communication states between hepatocellular carcinoma microenvironment cells that affect the prognosis and survival of patients. Using mitophagy-related gene classification, we predicted patient prognosis and guided treatment strategies. Our findings are expected to improve diagnosis, treatment, survival rates, and quality of life in hepatocellular carcinoma patients through targeted mitophagy intervention.